Influence of Progenitor‐Derived Regeneration Markers on Hepatitis C Virus–Related Cirrhosis Outcome (ANRS CO12 CirVir Cohort). Issue 4 (5th October 2018) - Wendum, Dominique; Layese, Richard; Ganne‐Carrié, Nathalie; Bourcier, Valérie; Merabtene, Fatiha; Cagnot, Carole; Sauce, Emmanuel; Barget, Nathalie; Bedossa, Pierre; Terris, Benoit; Selves, Janick; Bioulac‐Sage, Paulette; et al.
Abstract : Progenitor‐derived regeneration gives rise to the aberrant expression of biliary markers such as cytokeratin 7 (K7) and epithelial cell adhesion molecule (EpCAM) in hepatocytes. We aimed to describe the expression of these molecules in patients with compensated hepatitis C virus (HCV)–related cirrhosis and to investigate its potential influence on cirrhosis complications. Among patients with Child‐Pugh A uncomplicated HCV‐related cirrhosis enrolled in the prospective ANRS CO12 CirVir cohort, we selected individuals with a liver biopsy collected within 2 years before inclusion in the study. K7 and EpCAM immunostaining identified intermediate hepatobiliary cells. The influence of biliary marker expres‐sion in hepatocytes on decompensation events and the occurrence of hepatocellular carcinoma (HCC) was studied using a multivariate Cox proportional hazards regression model. Among the 337 patients eligible for the study (men, 67%; median age, 52 years), 198 (58.8%) had biopsies with K7‐positive hepatocytes including extensive staining in 40 (11.9%) and 203 had EpCAM‐positive hepatocytes (60.6%). During follow‐up (median, 54.2 months), 47 patients (14%) experienced a decompensation event, and HCC was diagnosed in 37 patients (11%). Extensive K7 staining was independently associated with the occurrence of a decompensation event (hazard ratio [HR], 3.00; 95% confidence interval [CI], 1.30‐6.89; P = 0.010). EpCAM expression was independently associated with HCC occurrence (HR, 2.37; 95% CI, 1.07‐5.23; P =0.033) along with age and a low prothrombin ratio. Conclusion: Progenitor‐derived regeneration depicted by K7 and EpCAM immunostaining of hepatocytes in liver biopsies of patients with compensated HCV‐related cirrhosis marks a cirrhosis stage more prone to develop complications. (HEPATOLOGY 2018; 68:1534‐1548).